The Best Practices of Mcdonald’s Malaysia: A Case Study of the National Dual Training System - Rohiat, Mohd Akmal; Chee Sern, Lai; Md Yunos, Jailani; Ibrahim, Badaruddin; Md Salleh, Kahirol; Rahim, Mohd Bekri; Rozali, Zulfadhli; Hamdan, Norhidayah; Janis, Ilyana; Primus, Marzita (Journal of Technical Education and Training, 2023)
The National Dual Training System (NDTS) was officially launched in February 2018 and there are five NDTS-approved McDonald’s practical training locations at the early implementation of the NDTS. By 2025, 450 McDonald’s Malaysia restaurants are expected to expand, adding 10,000 jobs to the current workforce of 12,000 employees. Based on the increasing number of employees and positive implementation of the NDTS program in McDonald’s Malaysia, this study aimed to explore the best practices of McDonald’s Malaysia in the context of NDTS. Methodologically, a qualitative approach was employed in this study by conducting a group discussion with the McDonald’s personnel, document analysis (such as news, annual reports, and websites) and a literature review. From the thematic analysis, the findings highlight the best practices of McDonald’s Malaysia and the positive implications of the NDTS implementation. A review of McDonald's training and skill development around the world provides additional support for the findings. Significantly, this study contributes to promote the best practices of McDonald’s Malaysia, the positive image of McDonald's Malaysia and the positive implications of NDTS in supporting skills development in Malaysia.